EMPOWERING RURAL ENTREPRENEURSHIP THROUGH MOTIVATION, TRAINING, AND HEXAHELIX SYNERGY - Purba, Golrida Karyawati; Suk, KIm Sung; Sembel, Jacquelinda Sandra (Journal of Sustainable Community Development (JSCD), 2024)
This community empowerment program aims to foster rural entrepreneurship using a motivational, training and synergy approach. This program is carried out in Pabuaran village, Gunung Sindur subdistrict, Bogor district, centered in Cikoleang. Motivational approaches are carried out formally and informally throughout the program. Enhancing entrepreneurial competence is carried out by providing training such as marketing, financial management and small business bookkeeping. To evaluate participants' entrepreneurial competence, this program assigns participants to prepare a business plan of interest. The entrepreneurial foster program has effectively increased entrepreneurial competence and synergy among entrepreneurial group members. An entrepreneurial group called Tunas CIkoleang was formed as a result of program implementation. Findings during program implementation conclude the importance of social capital, namely the strength of social relationships in fostering entrepreneurship in rural areas. Synergy is one of the factors that determines the success of community empowerment programs.